Técnicas de prospección uranífera aplicadas en la República Argentina - Friz, Carlos T.; Marinkeef, Kirilo; Coco, Alberto L.; Santomero, Angel M.; Muset, Jorge A. (Asociación Geológica Argentina; Argentina, 1974)
Fil: Friz, Carlos T. Comisión Nacional de Energía Atómica; Argentina